Development of a swimming humanoid robot for research of human swimming - Chung, C.; Nakashima, M. (Journal of Aero Aqua Bio-mechanisms, 2013)
In this study, the swimming humanoid robot SWUMANOID for research of human swimming was developed. It was half the size of a real human and had the same body proportions and appearance; mass distribution was considered, as well. It was actuated by 20 motors, which were waterproofed and compactly designed. Swimming motions were determined based on human swimming movements. To realize the swimming arm stroke, a joint imitating the human's scapular retraction was installed and the methodology to realize the swimming motion with that joint was established. Finally, the efficiency of the design was validated by simulation and representatively, the crawl stroke was successfully realized in the water tank.